Advanced Materials for Capturing Particulate Matter: Progress and Perspectives. Issue 7 (2nd May 2018) - Xiao, Jing; Liang, Jiachen; Zhang, Chen; Tao, Ying; Ling, Guo‐Wei; Yang, Quan‐Hong
Abstract: Particulate matter (PM) of different sizes is the prominent air pollutant that causes severe health issues. Despite source control, the removal of PM by porous materials is believed to be the most effective way of air purification. Extensive effort has been made toward the construction of advanced materials with both a high filtration efficiency and low pressure drop across them. Weight, transparency, thermal stability, and comfort in different environments are also key parameters for the practical use of such materials. Here, progress in the state of the art of materials for capturing particulate matter is summarized. Their structure, properties, and filtration mechanism are discussed. In addition, some possible directions for the future development of air filters, with regard to materials selection and structural design, are suggested. Abstract : The removal of particulate matter is of great significance for better air quality. Advanced air‐purification materials with various structures and composition are highlighted and their mechanisms are comprehensively summarized. Future prospects toward the materials design are proposed to make cleaner air.